Assessment of anomalous sentences repetition test. Issue 7 (July 1990) - Rai, G S; Stewart, K; Scott, L C
Abstract : Use of Anomalous Sentences Repetition Test (ASRT) in 16 patients with diagnosis of dementia of Alzheimer's type, 16 normal elderly and 18 patients with depression revealed no difference in the age adjusted scores between the three groups, suggesting that it is not a good test for diagnosing dementia or differentiating dementia from depression.